Legal regulation of the procedure for inheriting digital assets in cross-border inheritance relations - Artyshuk-Bereziuk, Larysa (Український політико-правовий дискурс, 2026)
The rapid development of digital technologies leads to a steady increase in the number of property rights that exist in digital form and have economic value. This trend creates a need for effective legal mechanisms for their inheritance, particularly in cases where succession relations are governed by the law of more than one state. The lack of a unified approach to the legal status of digital assets and to the procedures for their transfer by inheritance creates practical difficulties for heirs and law enforcement authorities. The purpose of the study is to determine the specific features of the legal regulation of the procedure for inheriting digital assets in cross-border inheritance relations, identify conflict-of-law issues, and formulate proposals for their resolution. The research applies general scientific and special legal methods, including the formal-logical method to define the conceptual framework, the comparative legal method to analyze approaches of different legal systems, the systemic-structural method to identify relationships between inheritance law and private international law norms, and legal modeling to develop proposals for improving legal regulation. It is established that digital assets are characterized by intangibility, dependence on technological platforms, and specific access conditions, which determine the particularities of their legal regime in inheritance law. It is established that the cross-border nature of inheritance requires determining the applicable law, jurisdiction, and mechanisms for recognizing heirs’ rights across different states. The key problems identified include the lack of a unified definition of digital assets, differing approaches to their qualification as objects of civil rights, and limited access for heirs to accounts and digital resources. The necessity of harmonizing the legal regulation of digital asset inheritance at the international level, establishing their legal status in national legislation, and developing procedures for heirs’ access to digital objects is substantiated. Directions for improving conflict-of-law rules and legal practice are proposed in order to ensure effective protection of inheritance rights in cross-border legal relations.